Genome Wide SNP Identification in Eucalyptus and its Application for Linkage Mapping and Adventitious Rooting Related QTL Analysis - Patturaj, Maheswari; Mayavel, A.; Dasgupta, Modhumita Ghosh; Nagarajan, Binai; Rajasugunasekar, D.; Sivakumar, Veerasamy; Yasodha, Ramasamy (Indian Forester, 2021)
Eucalyptus is a versatile genus with a particular significance for paper pulp, and it is extensively cultivated in India's marginal lands. Eucalyptus camaldulensis and E. tereticornis are highly preferred due to its optimal pulp yield, excellent fibre quality and good abiotic stress tolerance properties. Marker-assisted selections have played a major role in eucalyptus breeding programs. The use of genotyping-by-sequencing (GBS) approach for a largescale single nucleotide polymorphism (SNP) discovery and genotyping of an inter-specific mapping population, Eucalyptus tereticornis Ã— E. camaldulensis are reported in this study. Reduced representation libraries of 81 F1 progeny were sequenced and number of SNPs considered for linkage analysis was 96,377 single nucleotide substitutions, most of which (54.03%) represented transition events. Totally, 1999 and 4206 SNP markers were mapped to female (Eucalyptus tereticornis) and male (Eucalyptus camaldulensis) map, respectively. Consensus map consisting of 4844 markers were placed on a linkage map, which spanned 1367.6 cM and had an average of one marker every 0.29 cM corresponding to a physical distance of about 0.66 Mb. The map was utilized to identify six quantitative trait loci (QTLs) associated with adventitious rooting traits of stem cuttings accounting for phenotypic variations ranging from 7.18% to 9.17%. Analysis of the genomic sequence corresponding to six QTLs led to the identification of 201 putative candidate genes and 4 key genes were related to adventitious rooting specific expression. The integrated strategy utilizing the identified QTLs along with the available genome could serve as a platform for candidate gene identification for molecular breeding of eucalypts.